Crack formation of steel reinforced concrete structure under stress in construction period (Fracture and Structural Integrity, 2016)
To obtain deformation rules of steel reinforced concrete structure under stress, this study explored the crack formation in construction period. A novel structure system – steel reinforced concrete structure with shear wall and truss at the bottom was analyzed using on-the-spot test in combination with theoretical simulation analysis with SAP2000 software. It was found that, factors influencing crack formation of steel reinforced concrete structure in construction period included construction load, creep of concrete, shrinkage of concrete, displacement of bond of section steel and concrete as well as leveling. In the construction period, the simulated results and the measured results were highly fitted under the influence of time-variant characteristics such as compressive strength, elasticity modulus, creep and shrinkage. Through processing and analyzing the measured data, we obtained the development rules of crack formation of steel reinforced concrete structure with different strength grades as well as deformation rules of time-varying structure system in construction period, figured out the reason for the difference between the simulated results and the measured results, analyzed the deformation of structural components under stress in construction period and proposed some suggestions. This work is beneficial to ensure safe and high-efficient operation of construction.
Keywords: Crack; Steel reinforced concrete; Stress in construction period; Theoretical simulation analysis